The Impact of Digital Animated Flipbook on Knowledge and Adherence to Iron Supplementation: A Pre-Experimental Study Among Anemic Adolescent Girls - Indah Putri Ramadhanti; Desri Nova H; Kholilah Lubis; Debby Ratno Kustanto; Aini Mulia Hidayat (Journal of Ners and Midwifery, 2026)
Anemia remains a significant public health problem among adolescent girls in Indonesia, with low adherence to weekly iron-folic acid supplementation (IFAS) programs. Innovative educational strategies are needed to improve both knowledge and adherence to supplementation. This study aimed to examine the effect of CEMARA animated flipbook education on knowledge and weekly iron supplement adherence among anemic adolescent girls. A pre-experimental one-group pretest-posttest design was used. The study involved 68 ninth-grade anemic girls from SMPN 03 Bukittinggi, Indonesia. Consecutive sampling was applied to recruit participants. The intervention consisted of the CEMARA animated flipbook, which was delivered over one month. During this period, the girls also received weekly monitoring of their iron tablet intake. Knowledge and adherence were measured using structured questionnaires, both of which had acceptable reliability (Cronbach's alpha = 0.812 for knowledge and 0.803 for adherence). Data analysis was performed using the Wilcoxon signed-rank test and Spearman's rank correlation test. The mean knowledge score increased from 12.90 ± 2.306 to 19.13 ± 1.683 (p < 0.001). The mean adherence score increased from 3.56 ± 1.028 to 5.84 ± 1.016 (p < 0.001). However, the correlation between knowledge improvement and adherence was weak and not statistically significant (r = 0.171; p = 0.162). CEMARA animated flipbook education significantly improved knowledge and weekly iron supplement adherence among anemic adolescent girls. However, increased knowledge was not significantly associated with adherence, indicating that behavioral and contextual factors may also influence supplementation practices.